ANALYSIS OF THE NEEDS FOR INTERACTIVE LEARNING MEDIA BASED ON ARTICULATE STORYLINE 3 IN ENGLISH LEARNING IN ELEMENTARY SCHOOLS - Akmalia, Ngafiyatul; Alimuddin, Johar; Prahasto, Boby Sandityas (Program Studi Pendidikan Bahasa Inggris Fakultas ilmu Budaya, 2025)
English learning in the digital era requires the use of innovative and interactive learning media to improve the effectiveness of learning, especially in elementary schools. This study analysis the importance of developing interactive English learning media in elementary schools. The study used a qualitative method by conducting observations and interviews with teachers of MI 02 Mulyasari Majenang. The results showed that the learning media used were still one-way or not interactive. While many studies have shown that interactive learning media can make learning more interesting and effective. Therefore, interactive learning media are needed in English learning in elementary schools. One of the interactive media that can be used by teachers is media based on articulate Storyline 3.